A Case Study on The Mechanical and Durability Properties of a Concrete Using Recycled Aggregates - Khaoula Naouaoui; Toufik Cherradi (Civil Engineering Journal, 2021)
In Morocco, Recycled Aggregate Concrete (RAC) is not promoted unlike developed countries like France, Canada, US and many others. This article aims to present a Moroccan study related to the characterization of RAC and compare it with several studies all over the world. It focuses on compressive strength as the main mechanical characteristic and the porosity as the physical property that affects durability. The protocol is based on crushing concrete from demolished building and producing aggregates that are used in making experimental samples of RAC with different percentages of replacing Natural Aggregates (NA) by recycled ones. The first part of experimental study is to determine compressive strength of these samples after 7, 21, 28 and 90 days of confectioning it. Test results prove that above 25% of replacement level, the compression drops considerably and the Recycled Aggregates (RA) can’t replace the naturel ones. The second part of studies focuses on studying porosity as indicator of durability according to the performance approach. It concludes that the RAC may be used in a construction with a required life of 100 years specially building and roads. For high standards constructions or construction in a specific environment, more studies should be done. Doi: 10.28991/cej-2021-03091768 Full Text: PDF